PTU-138 Analysis of the effects of specialisation on the quality of reporting of stomach cancer using the Royal College of Pathologists minimum dataset in the Yorkshire region. (28th May 2012) - Rotimi, O; Morris, E
Abstract : Introduction: The completeness of a cancer pathology report is central to quality patient management and over the years proforma reporting has become a way of standardising reports. There has been an increasing trend towards specialisation in histopathology. This study examines the effect of specialisation on the degree of completeness, accuracy of information and quality of reporting of the Royal College of Pathologists' stomach cancer dataset. Methods: An audit of 1065 pathology forms from surgically removed stomach cancer cases over a 12-year period (1995–2006) was carried out. The rate of completeness of the forms, accuracy of the information content and quality of reporting were determined. Accuracy of the information content was adjudged by running specific queries to check for discrepancies such as mis-match of the depth of local invasion and the pathological tumour (pT) stage. Quality was assessed by the number of lymph nodes retrieved and recorded. The impact of specialisation on the accuracy and quality of the information contents of the forms were analysed by comparing median number of lymph nodes retrieved, completion rate of the forms and rate of discrepancies between specialist (Leeds) and non-specialist (11 others) departments. Differences between the two were statistically tested for significance (p≤0.05) using appropriate parametric and non-parametric tests. Results: Of the 1065 forms, 31% were submitted from Leeds NHS Trust. There was 90.3% completion rate for core items overall and there were discrepancies in 316 cases (30%). The number of lymph nodes retrieved range from 0 to 95 per case with an overall median of 15 lymph nodes. The results of the comparison between the specialist and non-specialist centres with respect to completeness, accuracy and quality are presented in Abstract PTU-138 table 1 . These showed statistically significant difference between the two groups with specialist centre consistently performing better than the non-specialist centres. Conclusion: This analysis of a large number of proformas from a region shows a completion rate and an overall good quality using lymph node retrieval. Specialisation of histopathologists has significant impact on the completeness of forms, accuracy of information content and quality of reporting. Therefore, further specialisation is recommended to improve the quality of cancer reports and patient management. Competing interests: None declared.